The involvement of L-type Ca(2+) channels in the relaxant effects of the ATP-sensitive K(+) channel opener ZD6169 on pig urethral smooth muscle - Teramoto, Noriyoshi (2001)
1. The effects of ZD6169, a novel ATP-sensitive K(+) channel (K(ATP) channel) opener, were investigated on membrane currents in isolated myocytes using patch-clamp techniques. Tension measurement was also performed to study the effects of ZD6169 on the resting tone of pig urethral smooth muscle. 2. Levcromakalim was more potent than ZD6169 in lowering the resting urethral tone. Relaxation induced by low concentrations of ZD6169 (⩽3 μM) was completely suppressed by additional application of glibenclamide (1 μM). In contrast, glibenclamide (1 – 10 μM) only partially inhibited the relaxation induced by higher concentrations of ZD6169 (⩾10 μM). 3. Bay K8644 (1 μM) reduced the maximum relaxation produced by ZD6169 (⩾10 μM). 4. In whole-cell configuration, ZD6169 suppressed the peak amplitude of voltage-dependent Ba(2+) currents in a concentration- and voltage-dependent manner, and at 100 μM, shifted the steady-state inactivation curve of the voltage-dependent Ba(2+) currents to the left at a holding potential of −90 mV. 5. In cell-attached configuration, open probability of unitary voltage-dependent Ba(2+) channels (27 pS, 90 mM Ba(2+)) was inhibited by 100 μM ZD6169 and by 10 μM nifedipine. 6. Reverse transcriptase-polymerase chain reaction (RT – PCR) analysis revealed the presence of the transcript of the α(1C) subunit of L-type Ca(2+) channels in pig urethra. 7. These results demonstrate that ZD6169 causes urethral relaxation through two distinct mechanisms, activation of K(ATP) channels at lower concentrations and inhibition of voltage-dependent Ca(2+) channels at higher concentrations (about 10 μM).